2016
DOI: 10.23939/chcht10.02.209
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining of Brown Pigments from Concentrated Waste Water Containing Nickel

Abstract: The possibility of obtaining brown pigments with the use of blast furnace slag from waste water containing nickel is justified. The scheme of the main reactions is proposed. The kinetics of the reactions is studied. The contribution of the chemical interaction into the overall degree of treatment is established by potentiometric titration. The influence of the main factors on the degree of nickel extraction is determined. The phase composition of the formed pigment is established with the help of X-ray analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
0
6
0
2
Order By: Relevance
“…In the works [15,[21][22][23][24][25] the analysis of wastes, that represents potential interest as a raw material for the production of pigments is made. The use of granulated blast furnace slag as a "core" is determined by high stability of the chemical composition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the works [15,[21][22][23][24][25] the analysis of wastes, that represents potential interest as a raw material for the production of pigments is made. The use of granulated blast furnace slag as a "core" is determined by high stability of the chemical composition.…”
Section: Resultsmentioning
confidence: 99%
“…Technology for brown color pigments production from concentrated waste water is described in detail in works [13][14][15]. A good alternative to commercial pigments synthesized from pure oxides are on iron oxides-based pigments obtained from pickling solutions [16].…”
Section: Introductionmentioning
confidence: 99%
“…Adsorbents of different nature, structure and mechanism of action are used to purify chromium-containing wastewater. For example, adsorbents commonly used to purify water from chromium cations are activated by carbon, silica gel, zeolite, clay minerals, slag [11][12][13][14][15]. However, these types of adsorbents have one common drawback -they require a long separation of solution, which increases operating costs.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, research in the field of adsorption technologies has shown interesting results for the treatment of concentrated wastewater from the industry. Today, adsorbents have been synthesized to remove heavy metal cations, including highly dangerous inorganic and organic substances [6,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%